Influence of Clinical, Psychological, and Psychophysical Variables on Long‐term Treatment Outcomes in Carpal Tunnel Syndrome: Evidence From a Randomized Clinical Trial. Issue 6 (23rd May 2019) - Fernández‐de‐las‐Peñas, César; de‐la‐Llave‐Rincón, Ana I.; Cescon, Corrado; Barbero, Marco; Arias‐Buría, José L.; Falla, Deborah
Abstract: Objective: To assess the influence of clinical, psychological, and psychophysical variables on long‐term clinical outcomes after the application of either physical therapy or surgery in women presenting with carpal tunnel syndrome (CTS). Methods: A secondary analysis of a randomized trial investigating the efficacy of manual therapy including desensitization maneuvers of the central nervous system against surgery in 120 women with CTS was performed. Clinical outcomes including pain intensity, function, or symptom severity were assessed at 6 and 12 months post‐intervention. Participants completed at baseline several clinical (pain intensity, function, and symptom severity), psychological (depression), and psychophysical (pressure pain thresholds and pain extent) variables, which were included as predictors. Multiple regression analyses were conducted to assess the relationship between baseline variables and clinical outcomes at 6 and 12 months post‐intervention. Results: The regression models indicated that higher scores of each clinical outcome (ie, intensity of pain or symptom severity) at baseline predicted better outcomes at 6 and 12 months post‐intervention (from 15% to 65% of variance) in both groups. Lower pressure pain thresholds over the carpal tunnel at baseline predicted poorer clinical outcomes at 6 and 12 months post‐intervention (from 5% to 20% of variance) in the physical therapy group, whereas higher depressive symptoms at baseline contributed to poorer outcomes at 6 and 12 months post‐intervention (from 5% to 15% of the variance) within the surgery group. Conclusion: This study found that baseline localized pressure pain sensitivity and depression were predictive of long‐term clinical outcomes in women with CTS following physical therapy or surgery, respectively.